Analysis of Compressed Natural Gas Burn Rate and Flame Propagation on a Sub-Compact Vehicle Engine - D., Ramasamy; K., Kadirgama; M. M., Rahman; Z. A., Zainal (Universiti Malaysia Pahang, 2015)
In terms of sub-compact cars using alternative fuels, the vehicle characteristics are governed by the engine operation. The main focus of this paper was to evaluate a subcompact car engine on its performance and burn rate of gasoline and compressed natural gas (CNG) . A bi-fuel sequential system was used for this evaluation. Measurements of engine speed, torque and fuel were done on an eddy current dynamometer, while measurements of in-cylinder pressure, crank angle and spark were analyzed from results taken by a data acquisition system. The emissions readings were also compared using an emission analyzer. The results were analyzed for burn rate based on the first law of thermodynamics. A 3-dimensional computational fluid dynamics (CFD) model was done to estimate the flame speed. The comparison shows an average drop of 18.6% for the power, 7% for brake specific fuel consumption (BSFC) and the efficiency loss was 17.3%. Pressure analysis shows peak pressure dropped by 16%. The burn rate shows why CNG had a slower burning speed on the small engine. CFD predicted the flame propagation speed at 8.45 m/s. The engine speed of 4000 rpm at maximum brake torque produced the results nearest to those for gasoline. In conclusion, volumetric losses and CFD errors slightly reduce the accuracy of the results, but nevertheless an 8.45 m/s flame speed was estimated.